PENTINGNYA PEMBELAJARAN TATA CARA SHALAT DAN THAHARAH MELIPUTI WUDHU, TAYAMMUM DAN MANDI WAJIB: STUDI FENOMENIAL PESERTA DIDIK - Ni’mah Wahyuni; Adi Friansa; Fajri; Haikal; Kasmiati (CV. ALIM'SPUBLISHING, 2023)
Knowledge and understanding of prayer and thaharah which includes Wudhu, Tayammum and obligatory bathing are important aspects in religious learning material in junior high schools (SMP). This discussion is about the importance of learning prayer and thaharah which includes ablution, tayammum and obligatory bathing as part of the implementation of religious education courses. Learning prayer and thaharah which includes obligatory ablution, tayammum and bathing at school not only ensures students' correct and consistent understanding of Islamic worship practices, but can also help in forming students' character and moral values. This also highlights the positive impact of this learning integration, such as increasing religious awareness, strengthening students' religious identity. Therefore, learning prayer and thaharah which includes ablution, tayammum and obligatory bathing for students has significant suitability in supporting the spiritual and moral development of students.